Increasing Strategies Sales MSMES Product of XBAG Malang Digitally Through E-Commerce - Dharma, Buyung Adi; Sudarmiatin, Sudarmiatin (International Journal of Business, Law, and Education, 2024)
The purpose of this study is to understand the digital marketing strategies used by the e-commerce project "XBAG MALANG" to increase its bag sales. This study was conducted using qualitative methods and a case study design. Information is collected through interviews, observations, and interviewing. The subjects are the owners and employees of the enterprise "XBAG MALANG". Research results show that "XBAG MALANG" adopts digital marketing strategies such as product optimization, marketing, and customer service. However, existing SEO optimization, product differentiation, cataloging, and customer service management strategies were not effective. The digital marketing strategy of "XBAG MALANG" still faces financial and manpower constraints. Therefore, it is recommended that XBAG MALANG improve human skills and understand digital marketing, adopt new technologies and analyze customer information to optimize strategies and increase product sales.